Analisa Usability Pada Aplikasi Identitas Kependudukan Digital Menggunakan Metode Usability Testing - Ernawati, Siti; Rahayu, Septi (BIOS : Jurnal Teknologi Informasi dan Rekayasa Komputer, 2024)
The digital population application is an application managed by the Directorate General of Population and Civil Registration under the Ministry of Home Affairs. This application serves to convert physical documents into digital format, making them accessible anywhere using smartphones. The existence of this digital population application is expected to facilitate the process of managing population documents. However, some users have expressed complaints about the digital population application, including interface issues and system problems. Based on these issues, a usability analysis is needed to assess effectiveness, efficiency, and customer satisfaction. The method used for the analysis is Usability Testing, which employs two techniques: performance measurement to assess effectiveness and efficiency, and Retrospective Think Aloud technique to evaluate customer satisfaction. Through Usability Testing, it has been found that the digital population application scored below the minimum value for the effectiveness aspect, while the efficiency aspect obtained a score that meets the standard. As for customer satisfaction, the results from the questionnaire indicate an optimal outcome.